2015
DOI: 10.1007/s10067-015-3008-9
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the risk of systemic lupus erythematosus: an updated systematic review and cumulative meta-analysis

Abstract: Published articles reported controversial results about the association of smoking with the risk of systemic lupus erythematosus (SLE). A meta-analysis was performed to assess the aforementioned association and arrive at a more precise estimate of effect. A comprehensive search was performed to identify case-control or cohort studies (from 1990 to 2015) of the aforementioned association. The I (2) statistic was used to examine between-study heterogeneity. Fixed or random effect model was selected based on hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
2
39
0
1
Order By: Relevance
“…Cigarette smoking has been associated with SLE risk in several, but not all, past studies . Two past meta‐analyses of these studies have pointed to current smoking, more than past smoking, as increasing SLE risk . A recent prospective study demonstrated an increased risk of anti–double‐stranded DNA positive (anti‐dsDNA+) SLE, but not overall SLE, with current smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking has been associated with SLE risk in several, but not all, past studies . Two past meta‐analyses of these studies have pointed to current smoking, more than past smoking, as increasing SLE risk . A recent prospective study demonstrated an increased risk of anti–double‐stranded DNA positive (anti‐dsDNA+) SLE, but not overall SLE, with current smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the potential impact of tobacco exposure on the development and outcome of certain autoimmune diseases, in particular rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), have been carried out extensively during the last decade [3,4,13]. There are various studies demonstrated that cigarette smoking is associated with worse disease manifestations of SSc, but the role of cigarette smoking as a risk factor for disease susceptibility in SSc has been rarely reported.…”
Section: Smoking On the Susceptibility To Sscmentioning
confidence: 98%
“…These changes could eventually, in the course of years or decades, lead to the development of an autoimmune disease. Recently, smoking has been found to be an environmental risk factor for the development to autoimmune diseases, e.g., rheumatoid arthritis [3] and SLE [4]. Unfortunately, no studies has associated smoking with increased prevalence of SSc, but several associations with disease manifestations have been noted during the last decade.…”
Section: Introductionmentioning
confidence: 98%
“…69 Nevertheless, there are no definitive data that quantify the relative contributions of these environmental risk factors to disease development, onset or flare. 70 Among the environmental agents studied in SLE, cigarette smoke [71][72][73][74][75][76][77] and environmental air pollutants 78,79 have attracted significant interest. It should be appreciated that the detrimental effects of cigarette smoking also apply to marijuana smoking.…”
Section: Genetic and Environmental Factorsmentioning
confidence: 99%